ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENGEMBALIAN SAHAM PADA PERUSAHAAN YANG TERDAFTAR DI INDEKS LQ45 BEI - admin, DESY CAROLINE B11112034 (Jurnal Manajemen Update, 2016)
The interest towards capital markets has kept on increasing every year. One of the most popular investment forms in the capital market is stocks. The investors expect income or optimal return from their investment. Stock returns reflect the performance and future prospects of companies (issuers), so it is important for investors and companies to determine the factors that may affect the rise and fall of stock returns. This study aimed to analyze the effect of the stock beta (?), the debt policy (DAR) and the dividend policy (DPR) on the return of the stock of asset growth (AG) as a control variable on companies listed in the LQ45 index in the period of 2010-2014. The method of sample collection in this research is purposive sampling and the sample of 12 companies is obtained, with 60 total observation samples. The data analysis technique that is utilized to test the hypothesis is multiple regression analysis with regression autoregresive models or distributed lag models. This study was done using Eviews 9, Eviews 7 and SPSS version 16.0. as an analytical tool. The results showed that the effect of stock beta, debt policy and dividend policy on stock return is consistent before and after the use of control variable. Stock Beta (?) and debt policy (DAR) had a negative impact, but no significant effect on stock returns. On the other hand, the dividend policy (DPR) had a negative impact and significant with a significance level of 1% before the control variable and after the control variable on stock returns. Keywords: Stock Return, Stock